Importance of Pedagogical Practice in Teaching Satisfaction - Iturriaga, Inelia Caterina Villalobos; Garcia, Katherine Acosta; Castro-Ceacero, Diego; Hernandez, Paola Contreras; Gonzalez Sanzana, Alvaro (My University, 2025)
The motivation shown by teachers in the early stages of their professional development affects their future professional competence and adaptability to an occupational setting. This study explores the motivational variables that affect satisfaction with choosing a degree in pedagogy in Chile by comparing teachers in training with in-service teachers. A quantitative non-experimental and correlational-explanatory design was used, surveying 758 participants (328 teachers in training and 430 in-service teachers) using the FIT-Choice questionnaire. Results reveal that intrinsic motivations, such as the desire to work with children, teenagers, and previous teaching experiences, have a strong positive correlation with satisfaction in both groups. This reveals the importance of encouraging and strengthening practical experience in initial teacher training. Furthermore, the differences in the value of job security and social contribution reflect the evolution of motivation from initial teacher training up to professional practice.
Keywords: pedagogy; teaching practice; teaching education; occupational satisfaction; motivation